Study of Trade and Non-Trade Sale of Cement Industry - Lamare, Rikupaarlangi (ATLAS SkillTech University, 2024)
Max Cement is one of India’s youngest players in the cement manufacturing sector and is fast-tracking its way towards becoming an established name in the business. What began as a first commissioned cement plant in Nongsning village of Meghalaya in 2011, with a production capacity of one million tonnes, has today made Max cement North-East’s key player. The proximity to high-grade limestone gives the product a unique edge over its competitors. The plant uses state-of-the-art German and Japanese technology in manufacturing superior quality cement that has already captured the market. That’s why despite many other market leaders, it is only Max Cement, who has been lauded for its quality and commitment with three prestigious awards in the last 3 years – ‘Power Brands Rising Star 2012’, ‘India’s Most Promising Brand 2013’ and ‘Most Promising Cement Brand 2014’.
Project Report on Study of Trade and Non-Trade Sale of Cement Industry (2022-24) Under the Guidance of Prof. Nikita Nadkarni
Keywords: Japanese technology; Max Cemen